Analysis of Execution Mechanism of Scorpion Like Temperature Measuring Robot for Coke Oven - Yaxiong Ren; Qiang Gao; Haodong Zhang; Jiaolong Xue; Hongwei Yan (Jixie chuandong)
Aiming at the bad environment of coke oven top and low accuracy of manual temperature measurement， a scorpion like robot for coke oven temperature measurement is designed. The robot is composed of walking mechanism and actuator. The overall structure of the temperature measuring robot is modeled， the kinematics equation of the manipulator is solved and simulated and its motion trajectory is planned. The workspace of the furnace cover lifting mechanism is analyzed to obtain the reachable space range of the end manipulator. The robot physical prototype is made to verify the positioning of the robot temperature measuring manipulator， and the error is within 2 mm. The workspace verification of the cover lifting mechanism can realize the workspace obtained by Monte Carlo， which lays a foundation for actual temperature measurement.